MICROWAVE INTEGRATED CIRCUIT WITH ANTENNA - KOGA HISAYOSHI; IMAI TOSHIO (1990)
PURPOSE:To obtain a microwave-IC having an antenna with small size and low cost coping with two orthogonal polarized waves by providing an antenna element, two amplifier circuits and a switching circuit. CONSTITUTION:An output of the circuit for a linearly polarized wave reception is obtained from a terminal 7 via a cross dipole element (antenna element) 1, low noise amplifiers 2a, 2b for horizontal and vertical polarized wave output, pin diodes 3a, 3b, a frequency converter 5 converting one output of the diodes 3a, 3b into a signal at an intermediate frequency band by using a signal from a local oscillator, and an intermediate frequency amplifier 6. One of the pin diodes is turned on by the bias control and the other is turned off and one of horizontal and vertical waves is subject to reception processing. The circuit for receiving a circularly polarized wave is provided with a hybrid 8 forming a phase difference of 90 deg. to the output of the amplifiers 2a, 2b and a pin diode 3 of bridge configuration and one of right or left rotatory circularly polarized waves is subject to reception control by the bias control of the element on the side.